Health, money, commerce, and wealth : anthropological perspectives - Wood, Donald C.; Swamy, Raja (Emerald Publishing Limited, 2024)
Volume 43 of Research in Economic Anthropology covers an extensive range of important topics with an equally wide geographic perspective. Grounded in fieldwork undertaken in West Africa, Asia, Europe, and North and South America, articles are broadly concerned with money, commerce, and wealth, with special concentrations on health, work, and uncertainty. Featured topics include: Connections between psychosocial health and anguish over educational expenses in Ghana's Upper West Region The upsurge of cryptocurrency trading in Istanbul, Turkey, in the face of uncertainty and where concern for the future translates into action in the present Personal transactions embedded in social relations from the perspective of a small-scale informal lender in Bangkok, Thailand The activities of finance elites in Luxembourg, now a major Western European center of commerce Work strategies of people who identify as self-employed in North Carolina and upstate New York during the COVID-19 pandemic Recent transformations in the lives of the Xambioá people in Brazil, including a reminder of how the sociocultural meaning of money can often take precedence over its intrinsic value or utility A novel proposal for eradicating poverty on a global scale Exploring the interconnectedness and uncertainty of today's economic world, this volume thoughtfully considers core themes, current trends, and possibilities for the future.
Keywords: Economic anthropology.; Social Science -- Anthropology -- General.; Economics.; Anthropology.; elektronické knihy; electronic books